Oridonin attenuates low shear stress-induced endothelial cell dysfunction and oxidative stress by activating the nuclear factor erythroid 2-related factor 2 pathway - Zhipeng Chen; Heqian Liu; Xiaoqi Zhao; Subinur Mamateli; Cheng Liu; Lei Wang; Jing Yu; Yutong Liu; Jing Cai; Tong Qiao (BMC, 2022)
Abstract Background Atherosclerosis (AS) is the primary cause of cardiovascular disease and the incidence is extremely common; however, there are currently few drugs that can effectively treat AS. Although oridonin has been widely used to treat inflammation and cancer for numerous years, to the best of our knowledge, its protective effect against AS has not been reported. Therefore, the present study aimed to investigate whether oridonin attenuated AS. Methods By using text mining, chemometric and chemogenomic methods, oridonin was predicted to be a beneficial agent for the treatment of AS. A parallel flow chamber was used to establish a low shear stress (LSS)-induced endothelial cell (EC) dysfunction model. Briefly, ECs were exposed to 3 dyn/cm2 LSS for 30 min and subsequently treated with oridonin or transfected with a small interfering RNA (siRNA) targeting nuclear factor erythroid 2-related factor 2 (NRF2). Reactive oxygen species (ROS), superoxide dismutase (SOD), malondialdehyde (MDA), glutathione (GSH) and glutathione disulfide (GSSG) in EA.hy926 cells were analyzed to determine the level of oxidative stress. The nitric oxide (NO) levels and mRNA expression levels of endothelial NO synthase (eNOS), endothelin-1 (ET-1) and prostaglandin synthase (PGIS) in EA.hy926 cells were analyzed to determine EC dysfunction. Furthermore, the mRNA and protein expression levels of NRF2 were analyzed using reverse transcription-quantitative PCR and western blot. In addition, zebrafish were fed with a high-cholesterol diet to establish a zebrafish AS model, which was used to observe lipid accumulation and inflammation under a fluorescence microscope. Results We found LSS led to oxidative stress and EC dysfunction; this was primarily indicated through the significantly decreased SOD and GSH content, the significantly increased MDA, GSSG and ROS content, the upregulated mRNA expression levels of ET-1, and the downregulated NO levels and mRNA expression levels of eNOS and PGIS in ECs. Notably, oridonin could improve LSS-induced oxidative stress and EC dysfunction, and the effects of oridonin were reversed by the transfection with NRF2 siRNA. Oridonin also attenuated lipid accumulation and neutrophil recruitment at the LSS regions in the zebrafish AS model. Conclusions In conclusion, the results of the present study suggested that oridonin may ameliorate LSS-induced EC dysfunction and oxidative stress by activating NRF2, thereby attenuating AS.